Knowledge, attitudes, and practices regarding the prevention of intracerebral hemorrhage among hypertensive patients - Qiang Chen; Feng Liu; LingLing Zhang; Yang Jin; Haibin Huang (Frontiers in Cardiovascular Medicine)
ObjectiveThe present study aimed to assess knowledge, attitudes, and practices (KAP) regarding the prevention of intracerebral hemorrhage among hypertensive patients and medication adherence to hypertension.MethodsWe conducted a cross-sectional study at the Third People's Hospital of Nantong City between November 4, 2023 and December 4, 2023. Demographic information, KAP and medication adherence scores were collected using an online questionnaire.ResultsTotally 600 valid questionnaires were analyzed. Among these, 443 participants (73.83%) were female, with a mean age of 62.95 ± 15.07 years. The mean scores for knowledge, attitude, practice, and medication adherence were 13.93 ± 2.88, 32.10 ± 3.22, 25.53 ± 3.44, and 3.12 ± 1.85, respectively. Only 3.50% had high medication compliance to hypertension. Multivariate analyses revealed that uncertain about family history of hypertensive intracerebral hemorrhage [OR = 0.378, 95%CI: (0.218–0.656); P = 0.001], no smoking [OR = 4.603, 95%CI: (1.954–10.845); P < 0.001], and no alcohol consumption [OR = 3.522, 95%CI: (1.764–7.033); P < 0.001] were independently associated with proactive practice. Structural equation modeling (SEM) results revealed direct effects between knowledge and attitude (β = 0.999, P < 0.001), knowledge and practice (β = 1.103, P < 0.001), as well as attitude and practice (β = 0.452, P < 0.001).ConclusionHypertensive patients demonstrated sufficient knowledge, positive attitudes, and inactive practices towards preventing intracerebral hemorrhage, coupled with poor medication adherence to hypertension. Developing targeted interventions to address these gaps and promoting a holistic approach is crucial to improving overall patient outcomes in clinical practice.